2022
DOI: 10.3390/cancers14174180
|View full text |Cite
|
Sign up to set email alerts
|

Role of Transmembrane Water Exchange in Glioma Invasion/Migration: In Vivo Preclinical Study by Relaxometry at Very Low Magnetic Field

Abstract: This work shows that the longitudinal relaxation differences observed at very low magnetic fields between invasion/migration and proliferation processes on glioma mouse models in vivo are related to differences in the transmembrane water exchange basically linked to the aquaporin expression changes. Three glioma mouse models were used: Glio6 and Glio96 as invasion/migration models and U87 as cell proliferation model. In vivo proton longitudinal relaxation-rate constants (R1) at very low fields were measured by… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
5
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
3
2

Relationship

4
1

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 45 publications
(79 reference statements)
2
5
0
Order By: Relevance
“…The method brings relevant information on the water cycling across the cell membrane related to the ongoing metabolism. The obtained results are consistent with previously reported observations made with a relaxometric approach lacking spatial resolution [56,57] . One can envision several applications for targeting and responsive agents that affect water proton relaxation rates whose changes can be efficiently detected through their impact on the intracellular CEST response.…”
Section: Discussionsupporting
confidence: 91%
“…The method brings relevant information on the water cycling across the cell membrane related to the ongoing metabolism. The obtained results are consistent with previously reported observations made with a relaxometric approach lacking spatial resolution [56,57] . One can envision several applications for targeting and responsive agents that affect water proton relaxation rates whose changes can be efficiently detected through their impact on the intracellular CEST response.…”
Section: Discussionsupporting
confidence: 91%
“…Tumour size estimation summarises the tumour size measurements obtained by all imaging modalities for all the patients. There was no statistically signi cant bias in the lesion size measured from FCI at ultra-low eld (in particular at 22 mT) compared to HE histology (39 [31][32][33][34][35][36][37][38][39][40][41][42][43] 5a, showing the regions corresponding to the tumour (as indicated by arrows), but larger in FCI than detected by MG and US. For P2, US, MG, and MRI detect only the invasive core (ILC, ROIs in blue), not showing the surrounding DCIS area.…”
Section: Fci Imagesmentioning
confidence: 90%
“…These agree with the literature, supporting the claim that T 1 relaxation at ultra-low elds in living tissues is a relevant biomarker discriminating invasion from non-invasion. This phenomenon is linked to the transmembrane water exchange, which has been found to be more rapid in tissues with glioma cells invasion 12,33 . Also, QP peak amplitudes were markedly higher for non-invasive tumours, although not signi cantly (0.9 [0.7-1.8] s − 1 in non-invasive vs 0.5 [0.06-1.0] s − 1 in invasive, Z = -1.5, p = 0.171, Fig.…”
Section: Fci Biomarkers Of Breast Cancer Invasionmentioning
confidence: 99%
“…One possible solution to the poor differentiation of glioma infiltration from surrounding edema is represented in the study by Zakharova and colleagues [ 193 ], who analyzed 50 cases of high-grade glioma and showed that diffusion kurtosis MRI biomarkers pinpointed structural tissue alterations in the brain tissue surrounding the tumor masses, delineating the invasive tumor borders in otherwise normally-appearing white matter. Moreover, Ruggiero and colleagues [ 194 ] conducted a preclinical evaluation of fast-field cycling nuclear magnetic resonance (FFC-NMR) and found that T1-relaxation at very low magnetic field through this sequence can successfully discern between proliferating and invasive/migrating glioma tissue, highlighting the promise of low-magnetic field relaxometry for future implementation in glioma patients. Finally, Hu et al leveraged multi-parametric MRI techniques such as diffusion tensor imaging (DTI) and dynamics susceptibility contrast MRI (DSC-MRI) and combined it with spatially-matched multi-omic analysis to characterize the biology of invasive non-enhancing tumor borders [ 195 ].…”
Section: Therapeutic Targets Of Glioma Invasionmentioning
confidence: 99%